Numerical Study on Shear Performance of a New Perfobond Connector with Controllable Stiffness - Yangqing Liu; Yuqing Liu; Haohui Xin; Hao Tian; Jun Wei (Advances in Materials Science and Engineering)
To improve the shear behavior and design applicability of rubber ring perfobond connectors (RPBLs), a new rubber ring that aims to make the shear stiffness of RPBLs controllable was proposed. Firstly, the conceptual design and configuration of the new rubber rings were presented and discussed. Subsequently, finite element (FE) models for modified push-out tests of new RPBLs were established based on the validated modeling method. The initial shear stiffness is dominated by the horizontal projected contact area between hole walls and concrete dowels. γ is defined as the ratio of the horizontal projected length of hollows to the diameter of holes. The shear stiffness of new RPBLs is about 35%, 60%, and 82% of the shear stiffness of PBLs when γ equals 0.25, 0.5, and 0.75, respectively. Employing the new rubber rings with varying central angles on conventional PBLs is feasible to obtain the required stiffness for RPBLs. Further, the effects of the number of sectors, the size of side wings, the central angle of hollows, the offset angle, and the thickness of rubber rings were analysed. Based on the numerical results, the proper thickness of side wings is no larger than 2 mm. The thicker side wing could reduce the confinement effects provided by surrounding concrete on concrete dowels, resulting in a drop of the yield load of new RPBLs. The number of sectors is suggested to be no less than 6 so that the shear behavior of new RPBLs is irrelevant to the offset angle. Besides, the shear stiffness is not related to the thickness of rubber rings. To improve the yield load of RPBLs and obtain the moderate recovered stiffness, the thickness of rubber rings is recommended as 2 mm. Finally, the expression for the shear stiffness of new RPBLs was proposed.